2023
DOI: 10.3390/metabo13080965
|View full text |Cite
|
Sign up to set email alerts
|

Liver Metabolomics and Inflammatory Profiles in Mouse Model of Fentanyl Overdose Treated with Beta-Lactams

Fawaz Alasmari,
Mohammed S. Alasmari,
Mohammed A. Assiri
et al.

Abstract: Fentanyl is a highly potent opioid analgesic that is approved medically to treat acute and chronic pain. There is a high potential for overdose-induced organ toxicities, including liver toxicity, and this might be due to the increase of recreational use of opioids. Several preclinical studies have demonstrated the efficacy of beta-lactams in modulating the expression of glutamate transporter-1 (GLT-1) in different body organs, including the liver. The upregulation of GLT-1 by beta-lactams is associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Up-regulation of glycolysis would lead to enhanced transamination of pyruvate to alanine, justifying the high levels of this amino acid in treated animals. A recent study by Alasmari et al 36 , in mouse model of fentanyl overdose (50 µg/kg i.p) suggested the involvement of glucose-alanine cycle and gluconeogenesis in liver metabolism alterations associated to increased liver inflammation, after a treatment with a fatal dose of fentanyl. These findings suggest that the increasing amino acids in urine samples of mice treated with fentanyl and morphine could be related to a protective response against increased inflammations triggered by these opioids in different organs 37 .…”
Section: Resultsmentioning
confidence: 98%
“…Up-regulation of glycolysis would lead to enhanced transamination of pyruvate to alanine, justifying the high levels of this amino acid in treated animals. A recent study by Alasmari et al 36 , in mouse model of fentanyl overdose (50 µg/kg i.p) suggested the involvement of glucose-alanine cycle and gluconeogenesis in liver metabolism alterations associated to increased liver inflammation, after a treatment with a fatal dose of fentanyl. These findings suggest that the increasing amino acids in urine samples of mice treated with fentanyl and morphine could be related to a protective response against increased inflammations triggered by these opioids in different organs 37 .…”
Section: Resultsmentioning
confidence: 98%
“…In addition, exposure of hippocampal cultures to morphine induced increases in neuroinflammatory cytokines, including IL-6 ( Osmanlioglu et al, 2020 ). Alternatively, a recent study from our group revealed that exposure to repeated exposures to fentanyl moderate dose followed by higher dose of fentanyl induced increases in IL-6 in liver, and this effect was attenuated by ceftriaxone treatment ( Alasmari et al, 2023 ). In the present study, both MC-100093 and ceftriaxone attenuated morphine-induced increase in IL-6 mRNA expression in the NAc.…”
Section: Discussionmentioning
confidence: 99%